Chemodenitrification in the cryoecosystem of Lake Vida, Victoria Valley, Antarctica. Issue 6 (14th July 2016) - Ostrom, N. E.; Gandhi, H.; Trubl, G.; Murray, A. E.
Abstract: Lake Vida, in the Victoria Valley of East Antarctica, is frozen, yet harbors liquid brine ( 20% salt, >6 times seawater) intercalated in the ice below 16 m. The brine has been isolated from the surface for several thousand years. The brine conditions (permanently dark, −13.4 °C, lack of O2, and pH of 6.2) and geochemistry are highly unusual. For example, nitrous oxide (N2 O) is present at a concentration among the highest reported for an aquatic environment. Only a minor 17 O anomaly was observed in N2 O, indicating that this gas was predominantly formed in the lake. In contrast, the 17 O anomaly in nitrate ( NO 3 − ) in Lake Vida brine indicates that approximately half or more of the NO 3 − present is derived from atmospheric deposition. Lake Vida brine was incubated in the presence of 15 N‐enriched substrates for 40 days. We did not detect microbial nitrification, dissimilatory reduction of NO 3 − to ammonium ( NH 4 + ), anaerobic ammonium oxidation, or denitrification of N2 O under the conditions tested. In the presence of 15 N‐enriched nitrite ( NO 2 − ), both N2 and N2 O exhibited substantial 15 N enrichments; however, isotopic enrichment declined with time, which is unexpected. Additions of 15 N– NO 2 − alone and in the presence of HgCl2 and ZnCl2 to aged brine at −13 °C resulted in linear increases in the δ 15 N of N2 O with time. As HgCl2 and ZnCl2 are effective biocides, we interpret N2 O production in the aged brine to be the result of chemodenitrification. With this understanding, we interpret our results from the field incubations as the result of chemodenitrification stimulated by the addition of 15 N‐enriched NO 2 − and ZnCl2 and determined rates of N2 O and N2 production of 4.11–41.18 and 0.55–1.75 nmol L −1 day −1, respectively. If these rates are representative of natural production, the current concentration of N2 O in Lake Vida could have been reached between 6 and 465 years. Thus, chemodenitrification alone is sufficient to explain the high levels of N2 O present in Lake Vida.